Traumatic posterior tibial artery occlusion in a soccer player: A case report - Aslim, Erdal (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2018)
A 24-year-old male professional soccer player sustained a right ankle contusion due to blunt kick toward the medial malleolus level during a soccer game. He stopped playing due to pain, coldness, and paresthesia on his right foot. Computed tomography angiography revealed a 4.5 cm occlusion on the posterior tibial artery at the right ankle level of which the distal segment was filled with collateral arteries. After the diagnosis of the traumatic occlusion, the patient underwent angiography for recanalization with thrombolysis in an external center, which was unsuccessful. Crural artery injuries after blunt sport traumas are very rare. In knee and ankle traumas with ischemic symptoms, vascular injuries should be excluded with prompt examination.
Keywords: Ankle; posterior tibial artery; soccer; trauma; vascular injury